Does fire induce flowering in Brazilian subtropical grasslands?. Issue 4 (14th March 2014) - Fidelis, Alessandra; Blanco, Carolina; Morgan, John
Abstract Questions We aimed to analyse the effect of fire on flowering in subtropical grasslands, by addressing the following questions: will fire history affect flowering? If yes, do fire feedbacks influence flowering or is it just the removal of above‐ground biomass? Are there differences in burned and mowed plots? Location Subtropical grasslands in Southern Brazil (30°03′S, 51°07′W). Methods We established plots in areas with different fire histories: 30 d (30 plots: five replicates), 1 yr (14 replicates), 3 yr (30 plots: five replicates) since the last fire, in experimentally burned and mowed plots (14 replicates each). We counted the number of flowering species, as well as the number of flowering stalks. Results Graminoid species flowered in highest numbers 1 yr after fire, whilst forbs had more species flowering just after fire, indicating different reproductive strategies in post‐fire environments. Mowing was not as efficient as fire in stimulating flowering. Finally, the different functional groups showed different flowering responses to time since last fire and to the different types of management. Conclusions Our results show fire stimulated flowering. Although mowing can be a good alternative for maintaining plant diversity, our study showed that this practice is not as efficient as fire in stimulating flowering. However, fire season should be noted as a limiting factor to the recovery of C3 grasses in these subtropical grasslands, and annual burns may be harmful to C4 grasses, since they delay their flowering to the next post‐fire growing season.